PENGARUH TINGKAT HUTANG DAN UKURAN PERUSAHAAN TERHADAP PERISTENSI LABA DENGAN BOOK TAX DIFFERENCES SEBAGAI VARIABEL MODERATING (Studi Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2016-2019) - Wuri Hastina (JURNAL ILMIAH EDUNOMIKA, 2021)
Abstract This study aims to examine whether the debt level and firm size has an effect on earning persistence. In addition, this study also aims to determine whether the book tax difference variable moderates the relationship between the variable debt level and firm size on earning persistence. The sample used in this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2016-2019. The number of samples in this study were 33 companies. The sample was selected using purposive sampling technique. This research uses quantitative descriptive method, for data analysis using multiple linear analysis and moderation analysis using the absolute difference value test with SPSS 20 software. The results of this study indicate that the level debt has a positive effect on earning persistence. Meanwhile, firm size has no effect on earning persistence. The results of the moderating variable indicate that Book Tax Differences as a moderating variable can weaken the debt level with earning persistence and firm size with earning persistence. Keywords : Debt Level, Firm Size, Earning Persistence, Book Tax Differences